Dark places - Flynn, Gillian 1971- (Crown Publishers, 2013)
For a price Libby Day will reconnect with the players that murdered her mother and two sisters in "The Satan Sacrifice of Kinnakee, Kansas." Having testified that her brother Ben was the murderer on that fateful night twenty-five years ago, now she is not so sure as, piece by piece, the unimaginable truth emerges, and Libby finds herself right back where she started--on the run from a killer.